نحو أمن لغوي مشروع لتمكين اللغة العربية - et-Tayyân, M. Hassân (Fatih Sultan Mehmet Vakıf Üniversitesi, 2020)
يقدِّم هذا البحث مقترحاتٍ للنهوض بالعربية، وتمكينها، وحمايتها، وإعادة المنزلة التي سلِبت منها، مبيّنا أهميتها في حياتنا، ومكانتها التي تنبغي لها، والأخطار المحدقة بها، والعداء المستحكم لها، وما أصابها من ضعف وهوانٍ وإهمال على أيدي أهلها. وفيما يأتي عناوين هذه المقترحات: • بثّ الوعي اللغوي. • إطلاق قانون حماية العربية. • إعادة التعريب )للوزارات والمصارف والجامعات والمؤسَّسات(. • إصلاح لغة الإعلام والإعلان وما شاكلها. • الارتقاء بتعليم العربية. • الإفادة من الصلة الوشيجة بين القرآن والعربية، ونشرها في أوسع نطاق ممكن. • إنشاء مؤسَّسات تُعنى بالعربية، وطرح مشاريع علمية تخدمها. • جعل إتقان اللغة العربية مطلبًا أساسيًّا للالتحاق بالجامعات، وبالدراسات العليا )توفل عربي على غرار توفل اللغة الإنجليزية(.

Bu araştırma, Arapça’nın geliştirilmesi, sağlamlaştırılması, himayesi ve i‘âde-i itibarı (hak ettiği konuma tekrar getirilmesi) ile ilgili bazı öneriler sunmaktadır. Öte yandan Arapça’nın hayatımızdaki önemine, olması gereken konumuna, Arapça’yı çevreleyen tehlikelere, kendisine yapılan husumete ve ehlinin eliyle uğradığı zayıflığa ve ihmalkârlığa değinmektedir. Önerilerin başlıkları: • Dil bilincinin yaygınlaştırılması • Arapça’yı koruma kanununun yürürlüğe girmesi • Kavramların yeniden Arapçalaştırılması (Bakanlıklar, bankalar, üniversiteler ve kurumlara yönelik) • Yayın ve basım dilinin iyileştirilmesi • Arapça öğretiminin geliştirilmesi • Kur‘ân-ı Kerîm ile Arapça arasında var olan sıkı ilişkiden istifade edilmesi ve bu faydanın olabildiğince geniş bir çerçevede yaygınlaştırılması • Arapça dil enstitülerin kurulması ve Arapça’ya hizmet eden bilimsel projelerin sunulması • Üniversiteye ve lisansüstü eğitime giriş sınavlarında Arapça’nın temel şart olarak koşulması (İngilizce TOEFL benzeri bir Arapça TOEFL yapılması)

This research provides proposals on how to enhance and protect the entity of Arabic, and restore the dignity which it once enjoyed. It also sheds light on the importance and the role of Arabic in everyday life in addition to the danger threatening it and the open hostility towards it. The study also shows the carelessness, heedlessness and thoughtlessness Arabic received at the hands of the Arabs themselves. The following list states some of these proposals: • Promoting linguistic awareness among the public. • Introducing legislation to protect the Arabic Language. • Pursuing a policy of Arabization in ministries, banks, universities and other institutions. • Rectifying the language of media and other public forms of advertisements. • Improving Arabic language education methods. • Highlighting and demonstrating the close relationship between the Quran and Arabic. • Founding some Arabic-related institutions whose role is to attend to the Arabic language and propose some projects in its favor. • Making the mastery of Arabic and the passing of an Arabic test, similar to TOEFL, a prerequisite for students willing to pursue university and postgraduate studies.
Dilin Muhafazası Yönünde Bir Adım: Arapçayı Yerleştirme Projesi
Towards Linguistic Safety
Keywords: الأمن اللغوي; الوعي اللغوي; حماية العربية; التعريب; Dilin Muhafazası; Dil Bilinci; Arapça’nın Korunması; Arapçalaştırma; Language Awareness; Arabic Protection; Arabization